Evaluación de Probióticos (ácido láctico, levadura de cerveza y hongos) sobre el desempeño de Parámetros Zootécnico para Pollos de Engorde. - Pilla Masaquiza, José Daniel (2018)
In the present project was carried out in the Province of Tungurahua, Pelileo Canton Salasaka Parish, Barrio Centro where the general objective was to evaluate probiotics (lactic acid, beer yeast and fungi) to improve the performance of zootechnical parameters of broilers in the area 3 development to the impact of different probiotics on zootechnical performance for fattening chickens since in our country and in the face experimental applications 4 treatments with 4 repetitions with a total of experimental units of 80 broilers of one day of age, at 14 days were distributed in four treatments and four repetitions in wooden boxes with an experimental unit of 5 chickens, distributed completely randomly (DCA), at least Witness was not given a diet without probiotic aggregation, at level T1 supplied a food diet With probiotics of lactic acid, T2 was given a dietary diet with probiotics. of brewer's yeast, T3 was supplied with a diet of mushrooms. The experimental project was divided into two phases: growth (0-21 days) and fattening (28-49 days). The evaluation method was used with the experimental results processed in Infostat and Excel, which were subjected to an analysis of variance (ADEVA) and Fisher's test for media separation with a significance of P <0.05 , which were initial weight which was homogeneous where the average was for T1 42.25 g, T2 42.35 g, T3 42.35 g and T4 42.10 the final weight determined that T4 reached an average weight of 2740, 00 g, followed by T3 with 2347.50 g, and T2 with 2294.75 g and less weight was T1 with 2027.50 g. The weight gain at the end of the project determined that the T4 reached an average of 2602.25 g, the T3 of 2275.00 and T2 of 2213.25 g, and the T0 of 2006, 50 g. The cumulative feed conversion determined at the end of the project that T4 has the best feed conversion with 2.57 g, T3 with 2.58 g, T2 with 2.59 g and the control with 2.63 g. The mortality of this project was 0%. The yield to the channel was the best the T4 (brewer's yeast) The cost-benefit of the treatments was the utility of T1 at $ 20.10, T2 of $ 30.10, T3 at $ 40.10 and with a higher percentage which was of T4 of $ 50.10. The conclusion of the project determines that with the addition of probiotics, better production parameters were obtained, unlike fungi and lactic acid, unlike the control This project met the expectations of the research that will serve as a reference for future research.